2013
DOI: 10.3138/ptc.2012-29
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive Programme of Passive Stretch and Motor Training to Manage Severe Knee Contractures after Traumatic Brain Injury: A Case Report

Abstract: Purpose: While contemporary management of contractures (a common secondary problem of acquired brain injury that can be difficult to treat) includes passive stretch, recent evidence indicates that this intervention may not be effective. This may be because clinical trials have not provided a sufficient dose or have not combined passive stretch with other treatments. The purpose of this case report is to describe a programme of intensive passive stretch combined with motor training administered over a 1.5-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Passive stretching and motor training have been widely used to prevent this complication. (15) Our study revealed that the patient's range of motion of the body's major joints was preserved without any statistically signi cant deterioration. The neurorehabilitative procedures helped to prevent the development of spasticity and rigidity.…”
Section: Outcomes Of Neurorehabilitation On the Range Of Motion Passi...mentioning
confidence: 54%
“…Passive stretching and motor training have been widely used to prevent this complication. (15) Our study revealed that the patient's range of motion of the body's major joints was preserved without any statistically signi cant deterioration. The neurorehabilitative procedures helped to prevent the development of spasticity and rigidity.…”
Section: Outcomes Of Neurorehabilitation On the Range Of Motion Passi...mentioning
confidence: 54%
“…These can also cause a delay in motor recovery, poor rehabilitation results, and prolonged hospitalization. Passive stretching and motor training have been widely used to prevent this complication [15]. Our study revealed that a patient's ROM in the body's major joints was preserved without any statistically significant deterioration.…”
Section: Outcomes Of Neurorehabilitation On Rom Passive Mobility and ...mentioning
confidence: 59%
“…Splinting can be gradually withdrawn over time as motor control and strength improve. 11,12 The findings of these two case studies provide justification for further research.…”
Section: Introductionmentioning
confidence: 79%